Polymers used in Vertebroplasty: The Importance of Material Technology in the Rehabilitation of Osteoporotic Patients - Corrêa, Daniela Gallon; de Araújo, Jonas Lenzi; Corrêa, Harrison Lourenço (Journal of Research Updates in Polymer Science, 2024)
Recent statistics show that the human population is tending towards aging. More effective medications and medical-hospital treatments, a more balanced diet, and regular physical activities contribute to longevity with quality of life.However, on many occasions, the natural aging process brings with it some chronic diseases, such as osteoporosis. Characterized by the loss of bone density, it can compromise mobility and even lead to death due to vertebral fractures, among other issues.To mitigate these risks, materials engineering becomes useful for restoring partial and/or total bone structure. In combination with a physiotherapeutic approach, they can rehabilitate the patient, providing them with a better quality of life.The present work aims to discuss the main polymeric materials used for the treatment of osteoporosis in patients with fractures.